Budd-Chiari Syndrome in a Patient with Hepatitis C - Joseph Frankl; Charles Hennemeyer; Michael S. Flores; Archita P. Desai (Case Reports in Hepatology)
Chronic Budd-Chiari syndrome can present with cirrhosis and signs and symptoms similar to those of other chronic liver diseases. We present a case of Budd-Chiari syndrome discovered during attempted transjugular intrahepatic portosystemic shunting in a patient with decompensated cirrhosis believed to be secondary to hepatitis C. Although the patient had hepatocellular carcinoma, the Budd-Chiari syndrome was a primary disease due to hepatic venous webs. Angioplasty was performed in this case, which resolved the patient’s symptoms related to portal hypertension. Follow-up venography 5 months after angioplasty demonstrated continued patency of the hepatic veins. A biopsy was obtained in the same setting, which showed centrilobular fibrosis indicating that venous occlusion was indeed the cause of cirrhosis. It is important to consider a second disease when treating a patient with difficult to manage portal hypertension.